Klimatyczne wyzwania Wspólnej Polityki Rolnej po 2013 r. - Błażejewska, Kamila (Wydawnictwo Naukowe UAM, 2011)
Climate change constitutes one of the most important challenges to CAP, thus we need to consider in what manner and scope climate change will be included in legal regulations concerning particularly agricultural markets and rural development. The author considers relationships between the agricultural sector and climate change and next characterises in more detail two directions for action, i.e. in terms of climate protection and actions in the adaptation of agriculture to climate change. Realisation of climatic challenges to CAP after 2013 is presented in view of factors determining the future form of this policy. In conclusion the author states among other things that CAP, being one of the most sensitive sector policies of the European Union, obtains additional legitimisation thanks to the incorporation of climatic challenge, which is common not only for the EU member countries, but all countries worldwide.

I cambiamenti climatici sono una delle sfide principali della PAC, per cui vale la pena di soffermarsi su come e in quale misura essi saranno presi in considerazione nelle regolazioni giuridiche riguardanti soprattutto i mercati agricoli e lo sviluppo rurale. L’Autrice considera i rapporti che intercorrono tra il settore agricolo e i cambiamenti climatici, quindi caratterizza più da vicino due linee di misure, ossia le misure per la protezione del clima e quelle per l’adattamento dell’agricoltura ai cambiamenti climatici. La realizzazione delle sfide climatiche della PAC dopo il 2013 viene presentata sullo sfondo dei fattori determinanti il futuro assetto di questa politica. In conclusione, l’Autrice afferma, tra l’altro, che la PAC, essendo una delle politiche settoriali più sensibili dell’Unione Europea, riceverà una legittimazione supplementare in virtù delle sfide climatiche comuni non solo agli Stati membri, ma a tutti i Paesi del mondo.